2022
DOI: 10.1002/smll.202206648
|View full text |Cite
|
Sign up to set email alerts
|

Salt‐Assisted Low‐Temperature Growth of 2D Bi2O2Se with Controlled Thickness for Electronics

Abstract: Bi2O2Se is the most promising 2D material due to its semiconducting feature and high mobility, making it propitious channel material for high‐performance electronics that demands highly crystalline Bi2O2Se at low‐growth temperature. Here, a low‐temperature salt‐assisted chemical vapor deposition approach for growing single‐domain Bi2O2Se on a millimeter scale with thicknesses of multilayer to monolayer is presented. Because of the advantage of thickness‐dependent growth, systematical scrutiny of layer‐dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 67 publications
(107 reference statements)
1
8
0
Order By: Relevance
“…In contrast to van der Waals (vdW) forces, Bi 2 O 2 Se exhibits relatively strong electrostatic forces between layers due to its alternately stacked positively charged [Bi 2 O 2 ] 2+ and negatively charged Se 2− layers along the c direction. 1,2 With a moderate bandgap ranging from 0.8 eV to 2.09 eV 3,4 and a high mobility of 28 900 cm 2 V −1 s −1 at 1.9 K and 450 cm 2 V −1 s −1 at room temperature, 5,6 along with high thermal and chemical stability, 4,7 Bi 2 O 2 Se holds great promise as a candidate for next-generation electronics, 8,9 optoelectronics, 7,10,11 thermoelectrics, 12,13 and ferroelectrics. 14,15 Furthermore, developing controllable large-area and high-quality 2D Bi 2 O 2 Se films speeds up the applications.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to van der Waals (vdW) forces, Bi 2 O 2 Se exhibits relatively strong electrostatic forces between layers due to its alternately stacked positively charged [Bi 2 O 2 ] 2+ and negatively charged Se 2− layers along the c direction. 1,2 With a moderate bandgap ranging from 0.8 eV to 2.09 eV 3,4 and a high mobility of 28 900 cm 2 V −1 s −1 at 1.9 K and 450 cm 2 V −1 s −1 at room temperature, 5,6 along with high thermal and chemical stability, 4,7 Bi 2 O 2 Se holds great promise as a candidate for next-generation electronics, 8,9 optoelectronics, 7,10,11 thermoelectrics, 12,13 and ferroelectrics. 14,15 Furthermore, developing controllable large-area and high-quality 2D Bi 2 O 2 Se films speeds up the applications.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Furthermore, developing controllable large-area and high-quality 2D Bi 2 O 2 Se films speeds up the applications. 7,10 Given the high demand for data storage, extensive research has focused on the ferroelectric properties of Bi 2 O 2 Se. [16][17][18] Ghosh et al reported the presence of ferroelectricity in 2 nm single-crystalline Bi 2 O 2 Se nanosheets through dielectric measurements and piezoresponse force spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…M n +1 X n T x ( n = 1 to 4) is a common formula for 2D MXene NMs, where M indicates transition metals (TMs) 3,5,6,13,20,49–80 and X indicates carbon or nitrogen, respectively 1,7–10,15,16,18,23,25,35,81–126 . Also, T x (where x varies) denotes single or mixed termination groups (for example, T = S, O, NH, F, Cl, Br, Te, OH, Se), as shown in Fig.…”
Section: Mxenes Introductionmentioning
confidence: 99%
“…Two-dimensional (2D) materials have attracted considerable attention as interesting candidates for numerous applications since the discovery of graphene. , Theoretical studies and experimental studies have contributed to expand the number of known 2D materials and improve our atomistic understanding of their electronic, , optical, , and structural properties. , The use of 2D materials in catalysis has emerged as a natural application due to the high surface area-to-volume ratio and the potential to tune their properties through defect engineering . For example, 2D materials have been employed as catalysts for diverse chemical reactions, including but not limited to the oxygen reduction reaction (ORR), , hydrogen evolution reaction (HER), , and oxygen evolution reaction (OER). , …”
Section: Introductionmentioning
confidence: 99%